2015
DOI: 10.1071/sr13339
|View full text |Cite
|
Sign up to set email alerts
|

Eucalyptus reforestation induces soil water repellency

Abstract: Abstract. There is an increasing interest in eucalypt reforestation for a range of purposes in Australia, including pulpwood production, carbon mitigation and catchment water management. The impacts of this reforestation on soil water repellency have not been examined despite eucalypts often being associated with water repellency and water repellency having impacts on water movement across and within soils. To investigate the role of eucalypt reforestation on water repellency, and interactions with soil proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 55 publications
0
22
1
Order By: Relevance
“…Few studies have reported so high persistence in water repellency with soil depth as found in this work. Walden et al (2015) found reforestation with E. globulus to induce water repellency across a range of sites in the southwest of Western Australia; contrary to our results, however, they also found SWR to decrease rapidly with increasing depth. Doerr et al (2006) examined water repellency in soils differing in texture, organic matter content, moisture and management regime at variable depths and concluded that the last two were reliable predictors for SWR.…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies have reported so high persistence in water repellency with soil depth as found in this work. Walden et al (2015) found reforestation with E. globulus to induce water repellency across a range of sites in the southwest of Western Australia; contrary to our results, however, they also found SWR to decrease rapidly with increasing depth. Doerr et al (2006) examined water repellency in soils differing in texture, organic matter content, moisture and management regime at variable depths and concluded that the last two were reliable predictors for SWR.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, inputs of organic matter from native vegetation induced SWR to a greater extent than equivalent amounts of organic matter from agricultural species (Harper et al 2000;Walden et al 2015). The contribution of specific residual organic compounds from former native vegetation to SWR in farmland soils is not known but may be significant and help to explain the spatially variable distribution of SWR in these soils (Harper et al 2000).…”
Section: Long-term Managementmentioning
confidence: 99%
“…Indeed, most likely the legacy of former native vegetation contributes to SWR rather than agricultural land use per se (Harper et al 2000). That said, SWR has been induced under plantation eucalypts established in lands previously used to grow annual pastures, which suggests its expression is sensitive to land-use and specifically to established vegetation (Walden et al 2015).…”
Section: Long-term Managementmentioning
confidence: 99%
“…Hence, water resources are under pressure in Chile. In particular, land cover changes alter catchment discharge, groundwater level and recharge rates (Huber et al ., ; Walden et al ., ) and thereby likely affect either the static or mobile water compartments in soil. In this study, we wanted to test (1) whether the TWW hypothesis holds for our study sites and (2) whether there is a difference in ecohydrological connectivity or (3) water sources (i.e.…”
Section: Introductionmentioning
confidence: 99%